FORMULASI DAN PEMBUATAN PAKAN PUYUH MENUJU KEMANDIRIAN PETERNAK DI DESA SUMBERINGIN KECAMATAN SANANKULON KABUPATEN BLITAR - Wardah Wardah; Tatang Sopandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
Sumberingin village, district of Sanankulon, Blitar city, East Java is one of the village that became center of poultry farms. This potential large farm was driving to the emergence of trade syndicate system of feed manufacturers, so it's easy playing the price and availability of animal feed. Beside that the spreading of low-quality animal feed was also being a potential problem. These conditions caused the farmers of suffering loss and even getting out of business. An observation indicated that the local area is a producer of potential animal feed raw materials such as tubers, legumes, tofu, soybean, molasses and bekicot/snails. Formulation science and technology of high quality animal food is needed by the farmers and it is a form of technology transfer to farmers group